Interpersonal Communication and Familial Harmony in the Sasak Ngelengkak Marriage Tradition: A Phenomenological Study In Central Lombok, Indonesia - Wisri Wisri; Shofiatul Ummah; Siti Raudhatul Jannah; Minan Jauhari (Journal of Social and Humanities, 2026)
Ngelengkak is a marriage-related tradition practiced within the Sasak community in Central Lombok, West Nusa Tenggara, Indonesia, in which a younger sibling marries before the elder sibling. Although frequently perceived as a culturally sensitive situation, the tradition remains socially accepted through particular forms of Interpersonal Communication and familial negotiation. This study investigates the meanings and Interpersonal Communication patterns embedded in the Ngelengkak tradition within Sasak society. Employing a qualitative approach with a phenomenological design, this research involved seven participants from the Sasak ethnic community in Central Lombok Regency. Data were collected through in-depth interviews and interpreted using phenomenological analysis to understand participants’ lived experiences and communicative interactions. The findings reveal that the Ngelengkak tradition is sustained through reciprocal two-way Interpersonal Communication characterized by dialogue, emotional negotiation, mutual respect, and collective decision-making among family members. These communication practices function as cultural mechanisms for reducing interpersonal tension, preserving kinship solidarity, and maintaining family harmony despite potential social stigma associated with marriage-order norms. The study further demonstrates that Interpersonal Communication within the Ngelengkak tradition reflects broader Sasak cultural values emphasizing social cohesion, familial respect, and communal balance. This research contributes to intercultural and family communication studies by highlighting how local marriage traditions operate as communicative spaces for negotiating social relationships and cultural continuity in contemporary Indonesian society.